Persepsi Simetode Mengajar Guru Pendidikan Agama Islam pada Siswa SMPN 3 Tanjung Medan - Pratama, Ilham Ade (EduInovasi: Journal of Basic Educational Studies, 2024)
This test expects to figure out understudies' perspectives on PAI teachers' presentation methods for understudies at SMPN 3 Tanjung Medan. This investigation method utilizes a realistic quantitative procedure. The populace in this study was 81 Muslim understudies at SMPN 3 Tanjung Medan. The assessment technique utilizes a full scale assessment, so the populace and test takers have similar number, to be specific 81 understudies. Data was gathered utilizing an open survey and a proportion of understudies' impressions of the teacher's exhibition procedure assessed utilizing a Likert scale. The data checking system utilized is realistic examination. Based on the consequences of data testing, the query items show that understudy appraisals are named 39.5% satisfied, 23.5% extremely fulfilled, 21% frustrated, and 16% exceptionally disheartened. Hence, one might say that the most predominant gathering of understudies' comprehension was satisfied at 39.5% and the gathering with the least understanding was exceptionally disheartened at 16%.